Brain wash : detox your mind for clearer thinking, deeper relationships, and lasting happiness - Perlmutter, David, 1954-; Perlmutter, Austin; Loberg, Kristin (Little, Brown Spark, 2020)
Contemporary life provides us with infinite opportunities, along with endless temptations. We can eat whatever we want, whenever we want. We can immerse ourselves in the vast, enticing world of digital media. We can buy goods and services for rapid delivery with our fingertips or voice commands. But living in this 24/7 hyper-reality poses serious risks to our physical and mental states, our connections to others, and even to the world at large. Brain Wash builds from a simple premise: Our brains are being gravely manipulated, resulting in behaviors that leave us more lonely, anxious, depressed, distrustful, illness-prone, and overweight than ever before. Based on the latest science, the book identifies the mental hijacking that undermines each and every one of us, and presents the tools necessary to think more clearly, make better decisions, strengthen bonds with others, and develop healthier habits. Featuring a 10-day bootcamp program, including a meal plan and 40 delicious original recipes, Brain Wash is the key to cultivating a more purposeful and fulfilling life.